Born into Care: characterising newborn babies and infants in care proceedings in England and Wales - Alrouh, Bachar; Broadhurst, Karen; Griffiths, Lucy; Johnson, Rhodri; Cusworth, Linda; Bedston, Stuart; Akbari, Ashley; Jones, Kerina; Ford, David (International Journal of Population Data Science, 2019)
Background/rationale Nations with advanced child protection systems place considerable emphasis on the developmental salience of infancy. However, this emphasis is not matched by any differentiated analysis of the timing of family court intervention in the lives of infants or the final legal order outcomes of these cases. This presentation shares findings from the first ever population profiling study of infants subject to care proceedings within the family justice system in England and Wales. Aim To estimate the proportion of all infant care proceedings cases issued within 7 days and 4 weeks of birth and describe case and infant characteristics; to calculate incidence rates over time and by local authority and family court region; to describe and compare legal order outcomes according to age. Methods/approach Data was extracted from case management records produced by the Children and Family Court Advisory and Support Service (Cafcass) England and Wales. Records were first restructured to link infants to legal order outcome data and birth mother records. Incidence rates were calculated using ONS mid-year population estimates and annual live births. Within the SAIL Databank, Welsh infant records were linked to birth registration and community child health data to produce a fuller picture of infant characteristics in Wales. Results The cohort we created comprised all infants recorded as subjects within care proceedings in England (2007/08-2016/17) and Wales (2011/12-2018/19). The study captured the high proportion of infant cases that are issued at/close to birth, but also marked regional and local authority variation in incidence rates. Conclusion High rates of adoption, particularly for babies born to mothers without a previous family court history, have prompted calls for new preventative solutions. The President of the Family (Court) Division in England has initiated a review of legal proceedings at birth.